Interhemispheric distribution of amyloid and small vessel disease burden in cerebral amyloid angiopathy‐related intracerebral hemorrhage. (31st May 2020) - Planton, M.; Pariente, J.; Nemmi, F.; Albucher, J‐F.; Calviere, L.; Viguier, A.; Olivot, J‐M.; Salabert, A‐S.; Payoux, P.; Peran, P.; Raposo, N.
Abstract : Background and purpose: Intracerebral hemorrhage (ICH) is a devastating presentation of cerebral amyloid angiopathy (CAA), but the mechanisms leading from vascular amyloid deposition to ICH are not well known. Whether amyloid burden and magnetic resonance imaging (MRI) markers of small vessel disease (SVD) are increased in the ICH‐affected hemisphere compared to the ICH‐free hemisphere in patients with a symptomatic CAA‐related ICH was investigated. Methods: Eighteen patients with CAA‐related ICH and 18 controls with deep ICH who underwent brain MRI and amyloid positron emission tomography using 18 F‐florbetapir were prospectively enrolled. In each hemisphere amyloid uptake using the standardized uptake value ratio and the burden of MRI markers of SVD including cerebral microbleeds, chronic ICH, cortical superficial siderosis, white matter hyperintensities and lacunes were evaluated. Interhemispheric comparisons were assessed by non‐parametric matched‐pair tests within each patient group. Results: Amyloid burden was similarly distributed across the brain hemispheres in patients with CAA‐related ICH (standardized uptake value ratio 1.11 vs. 1.12; P = 0.74). Cortical superficial siderosis tended to be more common in the ICH‐affected hemisphere compared to the ICH‐free hemisphere (61% vs. 33%; P = 0.063). Other MRI markers of SVD did not differ across brain hemispheres. In controls with deep ICH, no interhemispheric difference was observed either for amyloid burden or for MRI markers of SVD. Conclusions: Brain hemorrhage does not appear to be directly linked to amyloid burden in patients with CAA‐related ICH. These findings provide new insights into the mechanisms leading to hemorrhage in CAA.